THYROID CARCINOMA-ASSOCIATED GENETIC MUTATIONS ALSO OCCUR IN THYROID LYMPHOMAS - Aggarwal, Nidhi (2012)
Molecular testing for mutations activating the mitogen-associated protein kinase signaling pathway is being used to help diagnose thyroid carcinomas. However, the prevalence of these mutations in thyroid lymphomas has not been reported. Therefore, we studied the prevalence of BRAF, NRAS, HRAS, and KRAS mutations in 33 thyroid lymphomas and correlated the mutational status with the clinical, pathologic, cytogenetic, and immunophenotypic findings. Eleven cases were also tested for PAX8/PPARγ translocations. The lymphomas included 25 diffuse large B-cell lymphomas, 6 extranodal marginal zone lymphomas of mucosa associated lymphoid tissue type, and 2 follicular lymphomas. Seventeen diffuse large B-cell lymphomas were germinal center type, 6 non-germinal center type and 2 unclassifiable (Hans algorithm). None of the cases had an associated thyroid carcinoma. Mutations of the BRAF gene were identified in 6 (24%) diffuse large B-cell lymphomas (three D594G in germinal center diffuse large B cell lymphomas, two K601N in germinal center diffuse large B cell lymphomas, and one V600E in non-germinal center diffuse large B cell lymphomas) and of the NRAS gene in two (8%) non-germinal center diffuse large B-cell lymphomas (Q61K and Q61H). BRAF and NRAS mutations were not found in any extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue type or follicular lymphoma. HRAS and KRAS mutations were not identified in any of the cases, nor were PAX8/PPARγ translocations found. Thus, interpretation of finding a BRAF or NRAS mutation in the thyroid, particularly in preoperative thyroid aspirates, must take into account the differential diagnosis of a lymphoma. In addition to the diagnostic importance, our data also demonstrate that alteration in the mitogen-associated protein kinase pathway may play a role in the pathogenesis of some large B-cell lymphomas of the thyroid with potential therapeutic implications.